tDCS Over DLPFC Leads to Less Utilitarian Response in Moral-Personal Judgment - Zheng, Haoli; Lu, Xinbo; Huang, Daqiang (Frontiers in Neuroscience, 2018)
The profound nature of moral judgement has been discussed and debated for centuries. When facing the trade-off between pursuing moral rights and seeking better consequences, most people make different moral choices between two kinds of dilemmas. Such differences were explained by the dual-process theory involving an automatic emotional response and a controlled application of utilitarian decision-rules. In neurocognitive studies, the bilateral dorsolateral prefrontal cortex (DLPFC) has been demonstrated to play an important role in cognitive “rational” control processes in moral dilemmas. However, the profile of results across studies is not entirely consistent. Although one transcranial magnetic stimulation (TMS) study revealed that disrupting the right DLPFC led to less utilitarian responses, other TMS studies indicated that inhibition of the right DLPFC led to more utilitarian choices. Moreover, the right temporoparietal junction (TPJ) is essential for its function of integrating belief and intention in moral judgement, which is related to the emotional process according to the dual-process theory. Relatively few studies have reported the causal relationship between TPJ and participants’ moral responses, especially in moral dilemmas. In the present study, we aimed to demonstrate a direct link between the neural and behavioral results by application of transcranial direct current stimulation (tDCS) in the bilateral DLPFC or TPJ of our participants. We observed that activating the right DLPFC as well as inhibiting the left DLPFC led to less utilitarian judgements, especially in moral-personal conditions, indicating that the right DLPFC plays an essential role, not only through its function of moral reasoning but also through its information integrating process in moral judgements. It was also revealed that altering the excitability of the bilateral TPJ using tDCS negligibly altered the moral response in non-moral, moral-impersonal and moral-personal dilemmas, indicating that bilateral TPJ may have little influence over moral judgements in moral dilemmas.